EFFECTIVE APPLICATION OF FORMS AND TYPES OF ORGANIZATION OF EDUCATION IN PRIMARY GRADES - Nurmatova Madina Odiljon qizi; Islomova Maxsudaxon (Bright Mind Publishing, 2026)
This article deals with the issues of effective application of forms and types of organization of education in primary grades, coverage of students, increased interest of students in the lesson, organization of students' activities. The pedagogical significance of the organization of the educational process is analyzed, taking into account the age, psychological and individual characteristics of primary grade students. Forms of education, such as classroom, individual and independent work, are based on the role of students in the development of knowledge, skills and qualifications.
Keywords: Primary education, forms and types of organization of education, types and structure of the course, non-standard lesson.